The invertebrates smaller coelomate groups; chaetognatha, hemichordata, pogonophora, phoronida, ectoprocta, brachiopoda, sipuncula, the coelemate bilateria v.5. - Hyman, Libbie Henrietta (McGraw-Hill Book Company Inc., 1959)
McGraw-Hill Publications in the Zoological Sciences